Pengaruh Brand Ambassador dan Electronic Word of Mouth Terhadap Keputusan Pembelian - Anggraini, Dewi; Siregar, Onan Marakali (Peneliti.net, 2024)
The awareness of consuming healthy food is increasingly popular among the community, especially on Lemonilo Instant Noodles. The increase in purchasing decisions for Lemonilo Instant Noodles was heavily influenced by the presence of NCT Dream as brand ambassador. However, this effect was short-lived, resulting in a decrease in Lemonilo's sales. The decline in Lemonilo sales was also influenced by negative electronic word of mouth, which affected consumers' purchasing decisions. This study aims to examine the influence of brand ambassadors and electronic word of mouth on the purchase decisions of Lemonilo instant noodles in Medan. This study uses a quantitative method with an associative approach. The sample is taken using non-probability sampling with purposive sampling technique, involving 100 respondents as the sample. The primary data was obtained by distributing questionnaires directly and the secondary data were obtained through literature studies. The results of the study showed that the brand ambassador variable and the electronic word of mouth variable had a partial and simultaneous effect on the purchase decision of Lemonilo Instant Noodles in Medan. The coefficient of determination test shows that the relationship between brand ambassadors and electronic word of mouth on purchasing decisions is close, with an R-value of 0.755. Through the Adjusted R Square value, it's known that brand ambassadors and electronic word of mouth can explain purchasing decisions by 56,1%, the other 43,9% influenced by other variables outside the variables studied.